Analysis of the Laboratory Assistant Recruitment Selection Determination System using the TOPSIS Algorithm Method in the Computer Lab - Muhammad Azhar Syarif Arif (Journal of Information System and Artificial Intelligence, 2025)
Laboratory assistants are students appointed by the laboratory and accompany the lecturer during practical activities. The process for accepting computer laboratory assistants has several assessment criteria, both academic and non-academic. Errors in decision making cause distrust of computer laboratory assistants who are accepted and cause students to lack understanding and skills in certain subjects. This research for the selection of laboratory assistants is based on the TOPSIS method, which is a decision making method based on the idea that the option chosen is the best option that has the shortest distance to the positive ideal solution and the farthest distance to the negative ideal solution. There are five criteria used in selecting computer laboratory assistants, including GPA, semester, programming test, personality and interview. This research aims to provide recommendations as material for consideration for appropriate decision making and is expected to facilitate the process of selecting computer laboratory assistants that suit students' abilities, based on standard criteria and test results.